Suplementação mineral e vitamínica em dietas para alevinos de tilápia do Nilo - Camargo, Douglas Jardelino de (2013)
Vitamins and minerals are required in small quantities for fish growth, reproduction, health and metabolism. The aim of this study was to evaluate the influence of vitamin and mineral supplementation (VMS) in the diet of Nile tilapia. We used 540 fingerlings of Nile tilapia (0.91 ± 0.07 g), distributed in 18 cages of 1 m³ in a completely randomized design with six treatments (0, 0.25, 0.50, 1.00; 2.00 and 4.00% of VMS) and three replications during 116 days. The average water temperature in this period was 23.13 ± 3.00 ° C. At the end of the study, linear effects were observed (p <0.05) for the total length, standard length, weight gain and feed conversion, with better production for the level of 4.00% inclusion of supplement. Survival rates, carcass yield and hepatosomatic index were not affected (p> 0.05) by different supplementation. The hemoglobin, hematocrit, mean corpuscular hemoglobin and mean corpuscular volume were significantly different (p <0.05) among treatments, with higher values for the 4.00% SMV level. Erythrocytes and mean corpuscular hemoglobin concentration did not differ (p> 0.05) among the levels of VMS. We conclude that the level of 0.5% vitamin and mineral supplementation in diets for Nile tilapia improves performance and hematological parameters of fish.